2019
DOI: 10.3171/2018.6.spine161468
|View full text |Cite
|
Sign up to set email alerts
|

Location of correction within the lumbar spine impacts acute adjacent-segment kyphosis

Abstract: OBJECTIVEThe surgical correction of adult spinal deformity (ASD) often involves modifying lumbar lordosis (LL) to restore ideal sagittal alignment. However, corrections that include large changes in LL increase the risk for development of proximal junctional kyphosis (PJK). Little is known about the impact of cranial versus caudal correction in the lumbar spine on the occurrence of PJK. The goal of this study was to investigate the impact of the location of the correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…In the context of our findings, this is a very important observation, as the distribution of lordosis is increasingly recognized as a factor associated with outcomes. 28 - 30 Other than supine LL, our model also found that PI was an independent predictor of lumbar lordosis. Given that the cases in this study were performed within the past 5 years, this relationship is likely attributable to the clinical application of the past decade of ASD research, which has repeatedly demonstrated the intimate associations between pelvic parameters and LL.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the context of our findings, this is a very important observation, as the distribution of lordosis is increasingly recognized as a factor associated with outcomes. 28 - 30 Other than supine LL, our model also found that PI was an independent predictor of lumbar lordosis. Given that the cases in this study were performed within the past 5 years, this relationship is likely attributable to the clinical application of the past decade of ASD research, which has repeatedly demonstrated the intimate associations between pelvic parameters and LL.…”
Section: Discussionmentioning
confidence: 53%
“… 37 , 38 This has led researchers to propose that elderly patients should be fused with more thoracic kyphosis compared with their younger counterparts, a strategy recommended as a method to reduce mechanical complications. 13 , 28 The relationship between postoperative TK and supine LL is similar—research has shown that reciprocity between curves is necessary to restore the spine’s anatomic alignment. 39 Clinically, severe mismatch between TK and LL has been associated with poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As a whole, these results suggest that the loss of lumbar lordosis mainly occurs in the L4-S1 DLL. As a consequence, failure to restore DLL is correlated with an increased risk of proximal junctional failure [ 21 ], and DLL should be preserved or restored around 36° [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…36,62 Although historically L3 has been the most common level for lordosis restoration via PSO, emerging evidence suggests that restoring lordosis in a more physiological location (i.e., L4-S1) may be protective against PJK. 35 Orientation of the UIV and terminal rod contouring also appear to be important factors in PJK development.…”
Section: Pseudarthrosis and Instrumentation Failurementioning
confidence: 99%
“…Preplanned machine-bent rods may reduce junctional failures by helping to ensure that desired alignment corrections are achieved, including overall magnitudes of thoracic and lumbar curves, location of LL restoration (e.g., in the lower lumbar levels), and appropriate contouring of the proximal end of the rod. 34,35,84 An overall better definition of individualized alignment objectives, beyond simple age-adjusted objectives, could markedly reduce PJK. 32,36 In the future, more aggressive attention to bone optimization may also reduce junctional fractures.…”
Section: Advances To Further Reduce Complicationsmentioning
confidence: 99%